100 jaar samen wonen : jubileumboek Gentse Maatschappij voor de Huisvesting - Reynebeau, Guy; Putman, Marc; Van Keymeulen, Karel; Rawoens, Wouter (Gent: Gentse Maatschappij voor de Huisvesting, 2004)
"Guy Reynebeau, Marc Putman, Karel Van Keymeulen"